Managing diversity - Main, Wilson; Grinsted, Katherine (North Adelaide Video Communicators, 1994)
The video'looks at the need to create strategies and policies to eliminate discrimination; educate and train staff, monitor and evaluate progress regularly'...catalog
' Made in consultation with the Equal Opportunity Commission'
Cast: Indira Naidoo (presenter)
Keywords: Diversity in the workplace; Personnel management